Active layer thickening and controls on interannual variability in the Nordic Arctic compared to the circum‐Arctic. (14th October 2020) - Strand, Sarah M.; Christiansen, Hanne H.; Johansson, Margareta; Åkerman, Jonas; Humlum, Ole
Abstract: Active layer probing in northern Sweden, northeast Greenland, and central Svalbard indicates active layer thickening has occurred at Circumpolar Active Layer Monitoring (CALM) sites with long‐term, continuous observations, since the sites were established at these locations in 1978, 1996, and 2000, respectively. The study areas exhibit a reverse latitudinal gradient in average active layer thickness (ALT), which is explained by site geomorphology and climate. Specifically, Svalbard has a more maritime climate and thus the thickest active layer of the study areas (average ALT = 99 cm, 2000–2018). The active layer is thinnest at the northern Sweden sites because it is primarily confined to superficial peat. Interannual variability in ALT is not synchronous across this Nordic Arctic region, but study sites in the same area respond similarly to local meteorology. ALT correlates positively with thawing degree days in Sweden and Greenland, as has been observed in other Arctic regions. However, ALT in Svalbard correlates with freezing degree days, where the maritime Arctic climate results in relatively high and variable winter air temperatures. The difference in annual ALT at adjacent sites is attributed to differences in snow cover and geomorphology. From 2000 to 2018, the average rate of active layer thickening at the Nordic Arctic CALM probing sites was 0.5 cm/yr. The average rate was 1 cm/yr for Nordic Arctic CALM database sites with significant trends, which includes a borehole in addition to probing sites. This range is in line with the circum‐Arctic average of 0.8 cm/yr from 2000 to 2018.